Social Impacts of Costa Rica's PSA Program - Porras, Ina (World Bank, Washington, DC, 2014)
This paper discusses the social impacts of Costa Rica's Payments for Environmental Services (PSA) program and their effect on rural poverty. Although the analysis is hampered by significant information gaps, we believe that the PSA Program has probably managed to have an impact on the poor. This impact is almost certainly positive on the poor who were able to participate, but is difficult to quantify. However, except for very few cases, it seems unlikely that the PSA was able to actually lift participants out of poverty. Participation of the poor was initially low but increased as measures were introduced to target the poor and facilitate their participation.